The Enhancement of University Students’ English Vocabulary Acquisition through Memrise - Suryanti, Dewi; Fadli, Muhammad (Kognisi: Jurnal Ilmu Keguruan, 2025)
Vocabulary mastery is one of the key factors in improving English language skills, particularly for university students who are learning a foreign language at the tertiary level. However, based on observations of second-semester students in the Agribusiness Management Study Program at Politeknik Negeri Lampung, it was found that limited vocabulary remains a major obstacle to their ability to construct varied sentences effectively. To address this issue, this study implemented the Memrise application as a digital-based medium for vocabulary learning. Memrise was chosen due to its interactive features, which enable students to learn and retain new vocabulary more effectively through a gamification approach and spaced repetition. This study employed a quasi-experimental method with a pre-test and post-test design on a group of students who received treatment using Memrise. The results revealed that the use of Memrise had a significant positive effect on students’ vocabulary improvement. After the treatment, students were able to use a wider variety of vocabulary in constructing sentences, which directly contributed to greater complexity and diversity in the sentence structures they produced. These findings indicate that the integration of digital technology into language learning can serve as an effective strategy to enhance students’ competence, particularly in enriching vocabulary that supports their English communication skills.